2022
DOI: 10.1093/mnras/stac1003
|View full text |Cite
|
Sign up to set email alerts
|

Preparing for low surface brightness science with the Vera C. Rubin Observatory: Characterization of tidal features from mock images

Abstract: Tidal features in the outskirts of galaxies yield unique information about their past interactions and are a key prediction of the hierarchical structure formation paradigm. The Vera C. Rubin Observatory is poised to deliver deep observations for potentially of millions of objects with visible tidal features, but the inference of galaxy interaction histories from such features is not straightforward. Utilising automated techniques and human visual classification in conjunction with realistic mock images produc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 219 publications
0
22
0
Order By: Relevance
“…The plumes seen in the center of the cluster from ∼25 to 100 kpc (Figure 1) indicate that the BCG of this cluster is likely experiencing a merger (see also Duc et al 2015;Martin et al 2022). At the same time, the measured color is flat in the inner ∼100 kpc in both the east and west profiles, indicating that the stellar populations in this region are well mixed.…”
Section: Plumesmentioning
confidence: 88%
“…The plumes seen in the center of the cluster from ∼25 to 100 kpc (Figure 1) indicate that the BCG of this cluster is likely experiencing a merger (see also Duc et al 2015;Martin et al 2022). At the same time, the measured color is flat in the inner ∼100 kpc in both the east and west profiles, indicating that the stellar populations in this region are well mixed.…”
Section: Plumesmentioning
confidence: 88%
“…In our work, we focus on the flux fraction of tidal features ( f tidal ) and its distribution and try to establish the connection between flux fraction, visible time of tidal features, and merger rates of their hosts. Simulations have found that the detection rate of tidal features is dependent on the surface brightness limit and the projection angle (e.g., Ji et al 2014;Mancillas et al 2019;Martin et al 2022), so what we measured is certainly only the tip of the iceberg of fainter and more extended structures. However, these factors are hard to account for with observational data alone.…”
Section: Introductionmentioning
confidence: 65%
“…In our work, another factor contributing to this discrepancy is the mask we use in Section 3.2.3 to exclude clustered noise from the detection. Also, a significant fraction of tidal features are expected to extend to a galactocentric radius beyond 25 R eff for the most massive galaxies (Martin et al 2022), which is much larger than our choice (∼15 R eff ) in Section 3.3. The fact that we cannot detect tidal features at large galactocentric radii is also caused by the surface brightness limit, since tidal features gradually dissipate and become fainter as they move outward.…”
Section: Surface Brightness Limitmentioning
confidence: 76%
See 2 more Smart Citations